Introducing PSP (personal software process) in classroom (2010)
To consolidate a culture of software is necessary to have well defined processes and skilled personnel, trained in personal discipline and teamwork. Personal Software Process (PSP) contributes to individual labor discipline. This paper proposes a set of practical considerations to introduce the PSP, gradual and incremental manner in vocational training at the university in order to create the basis for introducing methods disciplined teamwork and meet the requirements of the industry. Some strategies are proposed for implementation at the University from the area of knowledge of algorithms and programming